2022
DOI: 10.7717/peerj.13564
|View full text |Cite
|
Sign up to set email alerts
|

Role of active joint position sense on the upper extremity functional performance tests in college volleyball players

Abstract: Background It has been well established that proprioception plays a decisive role in shoulder stability and sport performance. Notwithstanding, there is a lack of clear association between active joint position sense (AJPS) and the performance of upper-extremity functional performance tests. The aim of this study was to determine whether the AJPS of the shoulder complex is associated with the performance of college volleyball players with the following functional tests: Y-Balance Test-Upper Quarter (YBT-UQ), C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…In line with previous research [38][39][40], the findings of our study provide crucial insights into the profound functional deficits experienced by individuals with SIS when compared to a healthy control group. These deficits are evident in two fundamental aspects of shoulder function, namely, muscle strength and joint position sense, each playing a critical role in shoulder biomechanics and overall upper extremity function [41]. The reduced muscle strength observed among individuals with SIS is multifactorial.…”
Section: Discussionmentioning
confidence: 99%
“…In line with previous research [38][39][40], the findings of our study provide crucial insights into the profound functional deficits experienced by individuals with SIS when compared to a healthy control group. These deficits are evident in two fundamental aspects of shoulder function, namely, muscle strength and joint position sense, each playing a critical role in shoulder biomechanics and overall upper extremity function [41]. The reduced muscle strength observed among individuals with SIS is multifactorial.…”
Section: Discussionmentioning
confidence: 99%
“…This is relevant to the upper limbs, particularly to the glenohumeral (GH) joint, due to the sacrifice of joint stability [ 4 ] for a large range of motion [ 5 , 6 ]. Proprioception contributes to dynamic shoulder joint stability during upper limb activities such as sports [ 7 , 8 ], playing a musical instrument [ 9 ] and in daily activities (ADLs) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Y-upper body dynamic balance test (Y-UBDBT) in volleyball is a popular functional movement indicator to measure dynamic stability of the upper extremity in a weight-bearing position, thus identifying factors for risks of injury (23)(24)(25)(26)(27). It is well known that proprioception plays a decisive role in shoulder stability and motor control of the upper limbs (28). Proprioception includes sub-modalities like joint position sense (the ability to reproduce joint angles actively or passively), kinesthesia (sense of movement), sense of force, and sense of change in velocity (29,30).…”
Section: Introductionmentioning
confidence: 99%
“…A proprioceptive deficit could alter the recruitment of the shoulder muscles, causing an over-activation or under-activation of the rotator cuff muscles, ultimately predisposing an athlete to injury (31). Mendez-Rebolledo et al (28) evaluated possible correlations between shoulder position sense and the performance in the Y-UBDST in 18-26-year-old male and female college volleyball players who trained ≥ 12 hours per week. They observed that better results of active joint position sense at 90° of shoulder IR (when 90° of the arm abduction is present) are associated with the better performance of the Y-UBDST in superolateral, inferolateral direction, and composite score.…”
Section: Introductionmentioning
confidence: 99%